Reframing Domestic Violence Law and Policy: An Anti-Essentialist Proposal - Leigh Goodmark (Washington University Journal of Law & Policy, 2009)
This Article focuses on a central failure in domestic violence law and policy reform—the creation of a body of law and set of policies based on outmoded notions of what domestic violence is, the identities of the women who experience violence, the identities of their partners, and what such women need and want. The theoretical underpinnings of domestic violence law and policy largely are to blame for this excessively narrow and problematic view of domestic violence.
Keywords: Family violence; Feminist jurisprudence; Law reform; Abused women; Domestic violence; Feminism